A Model of Telecommunication Sector Development and Economical Growth in GCC Countries: A Case Study of UAE - Amiri, Shaima Yousef (2006)
A Master of Science Thesis in Engineering Systems Management by Shaima Yousef Amiri Entitled, "A Model of Telecommunication Sector Development and Economical Growth in GCC Countries: A Case Study of UAE," May 2006. Available are both Soft and Hard Copies of Thesis.